Co-precipitation method for the preparation of ferroelectric CaBi4Ti4O15 - Gaikwad, S. P.; Dhage, S. R.; Ravi, V. (Journal of Materials Science-Materials in Electronics, 2005)
A simple co-precipitation technique has been successfully applied for the preparation of pure single phase CaBi4Ti4O15 (CBT) powders. Ammonium oxalate and ammonium hydroxide were used to precipitate Ca2+, Bi3+ and Ti4+ cations simultaneously. No pyrochlore phase was found while heating powder at 600&DEG; C and pure CBT phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 400. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2005 Springer Science + Business Media, Inc.

Co-precipitation method for the preparation of fine ferroelectric BaBi2M2O9 - Gaikwad, S. P.; Potdar, HS; Samuel, V; Ravi, V (Ceramics International, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure fine powders of single phase BaBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was formed while heating powder at 800 degrees C and pure BaBi2Nb2O9 phase was found to be formed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Co-precipitation method for the preparation of nanocrystalline ferroelectric SrBi2Nb2O9 ceramics - Gaikwad, S. P.; Dhage, S. R.; Potdar, H. S.; Samuel, V.; Ravi, V. (Journal of Electroceramics, 2005)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase SrBi2Nb2O9. Ammonium hydroxide and ammonium oxalate were used to precipitate Sr2+, Bi3+ and Nb5+ cations simultaneously. No pyrochlore phase was found while heating powder at 850 C and pure SrBi2Nb2O9 (SBN) phase was formed as revealed by the X-ray diffraction (XRD) studies. Particle size and morphology was studied by transmission electron microscopy (TEM). The room temperature dielectric constant at 1 kHz is 100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic materials; ferroelectricity; Oxides

Preparation of nanocrystalline ferroelectric BaNb(2)O6 by citrate gel method - Gaikwad, S. P.; Samuel, V; Pasricha, R; Ravi, V (Bulletin of Materials Science, 2005)
A gel was formed when a aqueous solution of BaCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C yielded the nano crystallites of BaNb2O6, as confirmed by X-ray diffraction study (XRD). This is a much lower temperature as compared to that prepared by traditional solid state method (1000 degrees C) as reported for the formation of BaNb2O6. Transmission electron microscopic. (TEM) investigations revealed that the average particle size is 50 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1000. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Preparation of nanocrystalline ferroelectric CaBi2Ta2O9 by the urea method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Ceramics International, 2005)
A precipitate was formed when a aqueous solution of CaCl2, BiCl3, TaF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath. This precipitate on decomposition at 600 degrees C yielded the nanocrystallites of ternary oxide CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) were also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 70 nm. The room temperature dielectric constant was found to be 110. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders : chemical preparation

Preparation of nanocrystalline ferroelectric CaBi2TaO9 by citrate gel method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A gel was formed when an aqueous solution of CaCl2, BiCl3, TaF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600degreesC yielded the nano-crystallites of ternary oxide, CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) are also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 40 nm. The room temperature dielectric constant was found to be 90. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Bismuth; diffraction; Electron microscopy